Effect of Crude Oil Volatility Index (OVX) on the Energy Indices Return: Evidence from Wavelet Analysis - Mim, Tahmina Akther; Kathiravan, Chinnadurai; Maniam, Balasundram (International Journal of Economics and Financial Issues, 2025)
This study investigates the co-movement and causal relationships between crude oil volatility (measured by the OVX) and the returns of three Indian energy indices: BSE Oil and Gas, BSE Power, and CNX Energy. Employing statistical techniques such as descriptive statistics, ADF and Phillips-Perron unit root tests, OLS regression, and wavelet analysis, we examine the dynamic linkages between these variables. Our findings reveal a predominantly negative relationship between OVX and the returns of the analyzed energy indices. These insights provide valuable information for investors to make informed investment decisions, particularly considering the impact of weather conditions on energy markets. Furthermore, the findings offer valuable guidance for policymakers, investment analysts, and other market participants.